Economic burden of malaria on businesses in Ghana: a case for private sector investment in malaria control - Nonvignon, J.; Aryeetey, G.C.; Malm, K.L.; et al. (Malaria Journal, 2016)
Background: Despite the significant gains made globally in reducing the burden of malaria, the disease remains a major public health challenge, especially in sub-Saharan Africa (SSA) including Ghana. There is a significant gap in financing malaria control globally. The private sector could become a significant source of financing malaria control. To get the private sector to appreciate the need to invest in malaria control, it is important to provide evidence of the economic burden of malaria on businesses. The objective of this study, therefore, was to estimate the economic burden on malaria on businesses in Ghana, so as to stimulate the sector’s investment in malaria control. Methods: Data covering 2012–2014 were collected from 62 businesses sampled from Greater Accra, Ashanti and Western Regions of Ghana, which have the highest concentration of businesses in the country. Data on the cost of businesses’ spending on treatment and prevention of malaria in staff and their dependants as well as staff absentee‑ ism due to malaria and expenditure on other health-related activities were collected. Views of business leaders on the effect of malaria on their businesses were also compiled. The analysis was extrapolated to cover 5828 businesses across the country. Results: The results show that businesses in Ghana lost about US$6.58 million to malaria in 2014, 90 % of which were direct costs. A total of 3913 workdays were lost due to malaria in firms in the study sample during the period 2012–2014. Businesses in the study sample spent an average of 0.5 % of the annual corporate returns on treatment of malaria in employees and their dependants, 0.3 % on malaria prevention, and 0.5 % on other health-related corpo‑ rate social responsibilities. Again business leaders affirmed that malaria affects their businesses’ efficiency, employee attendance and productivity and expenses. Finally, about 93 % of business leaders expressed the need private sector investment in malaria control. Conclusions: The economic burden of malaria on businesses in Ghana cannot be underestimated. This, together with business leaders’ acknowledgement that it is important for private sector investment in malaria control, provides motivation for engagement of the private sector in financing malaria control activities.
Research Article
Keywords: Malaria control; Private sector investment; Economic cost; Ghana